The Obstinate Passion of Foreign Exchange Professionals: Technical Analysis - Menkhoff, Lukas; Taylor, Mark P (Journal of Economic Literature, 2007)
Technical analysis involves the prediction of asset price movements from inductive analysis of past movements. We establish a number of stylized facts, including that technical analysis is widespread in the foreign exchange market and that it may be profitable. We then analyze four arguments that have been put forward to explain this: that the market may not be fully rational; that technical analysis may exploit the influence of official interventions; that it may be an efficient form of information processing; and that it may inform on nonfundamental influences. While each may have some validity, the latter is the most plausible. As for the foreign exchange, it is almost as romantic as young love, and quite as resistant to formulae.